Oral immunization using live attenuated Salmonella spp. as carriers of foreign antigens. - Cárdenas, L (1992)
A variety of techniques, including the use of live oral vaccines, have been used to deliver antigens to the gut-associated lymphoid tissues in an attempt to initiate production of specific secretory immunoglobulin A for protection against pathogens that colonize or cross mucosal surfaces to initiate infection. A number of attenuated Salmonella mutants are able to interact with the lymphoid tissues in the Peyer's patches but are not able to cause systemic disease. Some of these mutants are effective as live vaccines (i.e., able to protect against infection with the virulent Salmonella parent) and are candidates for use as carriers for virulence determinants of other mucosal pathogens. This has been shown to be an effective means of stimulating significant levels of specific mucosal secretory immunoglobulin A directed against the carrier strains and against a variety of heterologous antigens and has been shown to stimulate production of serum antibodies and cell-mediated responses as well. This review examines the history of this mechanism of vaccine delivery and summarizes the most recent applications of this evolving technology. This is a technique for vaccine delivery with significant potential for influencing the management of infectious diseases on a large scale. It can be used not only for vaccines against enteric bacterial pathogens but also for vaccines against a variety of other bacteria, viruses, and parasites. The results obtained to date are encouraging, and there is great potential for development of safe, effective, affordable vaccines.